Numerical Simulation of Mechanical Characteristics of Roadway Surrounding Rock under Dynamic and Static Loading - Ce Jia; Sheng Li; Chaojun Fan; Jinbao Tang (Shock and Vibration)
Mechanical characteristics of roadway surrounding rock under different stress wave disturbances are the key to design roadway supporting scheme. In this study, the 2802 transportation roadway in Zhangcun Coal Mine is selected as the engineering background. The distribution of stress, displacement, and plastic zone in surrounding rock under the impact of different stress waves is studied. Results show that the stress and displacement of the roof, floor, and coal walls present fluctuating change with time during the stress wave loading process. With the increase of disturbing intensity of stress wave, the resistance ability for stress wave disturbance of the roof is lower than that of the floor, while the resistance ability of two sides is the same. The volume of plastic zone in roadway surrounding rock was calculated by the self-compiled FISH code. The relationship between the plastic zone volume and the stress wave disturbing intensity in different states is explored. The cubic polynomial relationship between the volume and the disturbing intensity in the state of shear_past and tension_past is obtained. Under the simulated condition, the disturbing intensity of stress wave has the greatest influence on the increase of shear_past volume when it equals 11 MPa. While the disturbing intensity of stress wave has the greatest influence on the increase of tension_past volume, it equals 7 MPa. Meanwhile, the relation between stress wave disturbing intensity and surrounding rock stress and displacement is obtained respectively. The achievements provide a theoretical base for roadway surrounding rock support under dynamic and static loading.